Meningkatkan Interaksi Guru Kristen dalam Pengembangan Kreativitas Anak - Hilda Gulo (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2024)
Early childhood we know that children who are still under the supervision, monitoring of adults, if in a family environment, parents play a role, and in a school environment the teacher plays a role in supervising children. In the interaction of teachers and students is very important to do because this helps a learning activity, or creativity carried out can succeed in achieving good and satisfying targets. The interaction relationship in the creativity activities that do this also builds better teacher and participant relationships. This interaction can be in the communication relationship between two individuals that the teacher and his students will do. The teacher has an important role in this interaction, which has a very large task and responsibility, because the teacher is not just standing in front of the class to convey material only, however, in the interaction activities carried out in creativity, the teacher as a guide, as a director, motivation and who always provides positive reinforcement to children. Children are encouraged to be more participatory, active, and given freedom in the activities that will be carried out. And children are freed to provide an idea - the ideas or ideas they have to be poured into every activity they will carry out. Because if the interaction approach to students is carried out continuously and well built, then the goals or targets can be achieved with good results.